Application of single-pass albumin dialysis in the acute phase of amanitin syndrome caused by mushroom poisoning - Jovanović, Dragana; Pilčević, Dejan; Isailović , Jelena; Perković Vukčević, Nataša; Vuković, Rade (Vojnosanitetski pregled, 2025)
Introduction. The frequency of mushroom poisoning is increasing both in the world and in our country. The most poisonous type of mushroom in our region is Amanita phalloides, which causes amanitin syndrome in poisoned patients, and it is considered responsible for the majority of deaths of patients intoxicated by mushrooms. The liver is one of the primary target organs of amatoxin toxicity. Clinical symptoms and signs of amatoxin poisoning manifest themselves in different ways and can range from simple gastrointestinal disorders to fatal outcomes. Currently, there is no knowledge in the literature about the existence of a specific antidote that should be used in the acute phase of amanitin syndrome. The basis of therapy is symptomatic and supportive therapy. Albumin dialysis is an extracorporeal, non-biological mechanism of liver function support used in liver failure of various etiologies. Case report. The initial treatment of a patient treated with the clinical picture of alimentary intoxication with mushrooms and amanitine syndrome included symptomatic and supportive therapy. Due to elevated values ​​of liver enzymes, as well as ammonia and present oliguria, a multidisciplinary analysis determined that single-pass albumin dialysis (SPAD) should be applied as a treatment measure in this patient to support hepatic and renal function. Following a temporary improvement, the general condition worsened upon continuing the treatment. That was manifested by a worsening of the state of consciousness and, consequently, the respiratory function. Further treatment included mechanical ventilation and repeated SPAD procedure. This eventually led to positive outcomes, including improved consciousness, better respiratory function, and normalization of laboratory indicators of liver and kidney function. Conclusion. Considering that liver function is compromised in amanitin syndrome, SPAD is a good choice in the treatment of a patient with a severe clinical picture of mushroom poisoning. The presented patient is the first mushroom-intoxicated patient with this severity of the clinical picture, treated at our institution, in whom no fatal outcome was recorded. Based on further tests or analyses and more clinical experience that will be gained with the further use of SPAD, it is necessary to create a clear protocol for the use of this method during the treatment of patients intoxicated by mushrooms.
Keywords: amanitins; dialysis; hepatic encephalopathy; hepatic insufficiency; mushroom poisoning